2012
DOI: 10.1016/j.eurpolymj.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar morphologies of hydrogels obtained from a lamellar medium

Abstract: Hydrogels are suitable for multiple applications and their properties are strongly dependent on their morphology. Sponge-like morphologies are obtained in conventional hydrogels when the polymerization is performed in isotropic media. Fibrillar morphologies imparting new properties to hydrogels are expected when the reacting medium is anisotropic. Here, we synthesize such fibrillar hydrogels by polymerization in a lamellar medium formed by 1,4-bis(2-ethylhexyl)sodium sulfosuccinate (AOT) and water. At high sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Additionally, a non-homogeneous distribution of the initiator in the different domains (hydrophobic or hydrophilic) could occur, leading to a modification of the expected characteristics of the polymer. It has been previously reported that X-rays act as an initiator in the polymerization of acrylamides, acrylates, or ethylene glycol . Besides, the high photon flux of synchrotron radiation provides a method to follow the polymerization process in situ, by the change in the scattering curves, from the initial mixture to the postpolymerized state .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a non-homogeneous distribution of the initiator in the different domains (hydrophobic or hydrophilic) could occur, leading to a modification of the expected characteristics of the polymer. It has been previously reported that X-rays act as an initiator in the polymerization of acrylamides, acrylates, or ethylene glycol . Besides, the high photon flux of synchrotron radiation provides a method to follow the polymerization process in situ, by the change in the scattering curves, from the initial mixture to the postpolymerized state .…”
Section: Introductionmentioning
confidence: 99%
“…In those aspects, polyarylate (PAR)/nylon6 islands‐in‐sea fibers are considered as suitable materials for manufacturing thermoplastic composites, because PAR island part acts as reinforcing microfibers and nylon6 sea part serves as a tough semicrystalline matrix in final thermoplastic composites. PAR with a rigid chain structure is known to be one of high‐performance engineering polymers exhibiting a liquid crystalline phase under melt state and its fibers have nanofibrillar structure, which is developed during melt‐spinning and following heat‐treatment process . Furthermore, PAR fibers do not retain moisture in humid or aqueous atmosphere and thus maintain stable physical properties when used as reinforcement materials.…”
Section: Introductionmentioning
confidence: 99%